PENGELOLAAN TAMAN NASIONAL BANTIMURUNG-BULUSARAUNG DAN DAMPAKNYA TERHADAP MASYARAKAT LOKAL - Robert Siburian (Jurnal Masyarakat dan Budaya, 2010)
Bantimurung-Bulusaraung (Babul) National Park was established in 2004. As a new national park, collaborative activities with surrounding community are still limited. Fixing the border line between the national park and the surrounding areas is still in the main preoccupation of the national park. The problem in Babul National Park is related to still unsolved land ownership. Local people in Dusun Tallasa claimed that the land had beenoccupied since a long time. Their ancestors had lived in the area before government proclaimed the forest as a conservation area. Besides, they also have evidence such as girik (traditional land ownership documents). Colaborative activities are limited and have not been based on memorandum of understanding. The only institution which collaborates with Babul National Park Office (Balai Taman Nasional Babul)is Tourism and Culture Agency (Dinas Pariwisata dan Kebudayaan)and Babul National Park Office (Balai Taman Nasional Babul). This paper aims to describe the real situation regarding the relation between Babul National Park Office and the local communities their economic activities, and the benefits that could be obtained by both the communities and ecosystem in regard to natural conservation goals. Keywords: stakeholders, collaborative management, environment, conflict, national park